Original article Changes of cytoskeletal proteins in ischaemic brain under cardiac arrest and reperfusion conditions - Sulkowski, Grzegorz; Strużyńska, Lidia; Lenkiewicz, Aleksandra; Rafałowska, Urszula (Folia Neuropathologica, 2006)
Folia Neuropathol 2006; 44 (2): 133-139 The aim of the study was to assess the level of calpain and its endogenous substrates – microtubule-associated protein 2 (MAP-2) and fodrin in the rodent model of global cerebral ischaemia caused by temporary cardiac arrest accurately mimics cardiac infarct and reperfusion in human. The effects of 10 min global ischaemia were measured immediately and in several post-resuscitation periods (1 h, 24 h, and 7 days). In Western blots we observed a significant, time-dependent increase in the expression of enzyme’s protein. The proteolytic effect of its activity was also time-dependent and evidenced 24 h after ischaemic episode as an increased level of 150-kDa a-fodrin breakdown product (FBDP). Parallel to these changes, expression of MAP-2 protein was lowered. Additionally, the electron microscopic studies of synapses showed a decreased number of synaptic vesicles early after ischaemic insult. In conclusion, our results show a temporal pattern of changes in calpain proteolytic activity and protein expression in the applied model of brain ischaemia caused by cardiac arrest and reperfusion. In these conditions calpain-mediated degradation of cytoskeleton may be involved in the disturbances in synaptic vesicles transport and hence to the changes in neurotransmission. cardiac arrest, reperfusion, global ischaemia, calpain, cytoskeletal proteins, MAP-2, α-fodrin